Discerning spirits: divine and demonic possession in the Middle Ages - Caciola, Nancy (Conjunctions of religion & power in the medieval past, 2006)
Possessed behaviors -- Ciphers -- Fallen women and fallen angels -- Breath, heart, bowels -- Exorcizing demonic disorder -- Testing spirits in the effeminate age